Gender differences in leucine kinetics and nitrogen balance in endurance athletes - Phillips, S. M.; Atkinson, S. A.; Tarnopolsky, M. A.; MacDougall, J. D. (Journal of Applied Physiology, 1993)
The current Canadian Recommended Nutrient Intake (RNI) for protein (0.86 g.kg-1.day-1) makes no allowance for an effect of habitual physical activity. In addition, Tarnopolsky et al. (J. Appl. Physiol. 68: 302-308, 1990) showed that males may catabolize more protein than females consequent to endurance exercise. We examined nitrogen (N) balance and leucine kinetics during submaximal endurance exercise to determine the adequacy of the current Canadian RNI for protein for male and female endurance athletes. Athletes were matched for equal training volume, competitive status, and conditioning and were fed diets isoenergetic with their habitual intake, containing protein at the Canadian RNI. Subjects were adapted to the diet for 10 days before completing a 3-day measurement of N balance. N balance showed that the RNI was inadequate for females (-15.9 +/- 6.0 mg.kg-1.day-1) and males (-26.3 +/- 11.0 mg.kg-1.day-1). Leucine kinetics during exercise were determined for each subject on day 3 of the N balance experiment by use of a primed continuous infusion of L-[1-13C]leucine and the reciprocal pool model. Exercise resulted in a significant (P < 0.01) increase in leucine oxidation for both groups. Males oxidized a greater amount of leucine during the infusion than females (P < 0.01). Leucine flux also increased significantly (P < 0.01) during exercise in both groups. We conclude that the current Canadian RNI for protein is inadequate for those who chronically engage in endurance exercise.